Consulting Activities of Internal Auditors in the Public Sector in Hungary - Kovács, Tamás (Public Finance Quarterly, 2022)
Today, internal auditors not only perform assurance activities but also provide consulting services. The internal audit consulting activities are services provided to heads of organisations, resulting in added value. This paper has been prepared with the objective to explore such activities for their importance and practical implementation in budgetary institutions, municipalities, and publicly owned companies. In the course of the study, primary research has been conducted, in addition to processing literature and legal regulations. We have found that the consulting role for supporting decision-makers as part of internal auditing has been reinforced with increased importance in the public sector as well. However, we have found that further steps could be taken to preserve independence and reinforce regularity and efficiency, for example, by giving a stronger focus to these subject matters through training programmes or providing more detailed recommendations.